First photographic record of the Rusty-spotted Cat Prionailurus rubiginosus (I. Geoffroy Saint-Hilaire, 1831) (Mammalia: Carnivora: Felidae) in Horton Plains National Park, Sri Lanka - Nimalrathna, TS (Wildlife Information Liaison Development Society, 2019)
10.11609/jott.4094.11.4.13506-13510